Pemberdayaan Guru Sekolah Dasar Melalui Pelatihan Literasi Mengembangkan Lingkungan Kaya Teks Multimodal - Sutarjo, Sutarjo; Bahrum Kamil , Acep; Ma'shum, Sya'roni Ma'shum; Haifa Zahra , Wafa; Irvi Nurul Husna, Ade (Sivitas : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
The program "Empowerment of Elementary School Teachers through Literacy Training to Develop a Multimodal Text-Rich Environment" aims to improve teachers' understanding and skills in integrating multimodal texts in learning. The methods used include preliminary studies, direct training, mentoring, and evaluation. The partner in this program is MIS Asasuttahdzibiyah in Tegalwaru District, Karawang Regency. The materials trained include the introduction of literacy and multimodal texts, the development of a multimodal text environment based on students, classes, and schools, as well as the formation of teacher study groups. The success factors of the program include comprehensive material delivery, interactive teaching methods, practical technical guidance, collaboration between teachers, and continuous evaluation. The results of the training showed a significant improvement in five main indicators of teacher skills, namely concept understanding, ability to integrate texts, use of technology, creativity in creating teaching materials, and collaboration. The outputs of this activity include improving teachers' skills, publishing training results, and forming a sustainable learning community to continue to support literacy development in elementary schools.